The Policy Process of Corporate Planning (Global Journal of Management and Business Research, 2013)
This article focuses on the policy process of corporate planning in Nigeria with emphasis on the relevance of planning as a panacea for business success. Research shows the existence of impediment on appropriate policy formulation and corporate planning which often result in premature business failure if unnoticed at the beginning stage. The research also uncover that some of these constraints are largely human error that could be corrected. This paper recommends the institution of budgetary discipline assessment of organization current strength weakness as a foundation for setting realization objectives, regular and adequate evaluation of performance against standard and making planning function a core top management responsibility amongst others.